1960 Meletean - University of Wisconsin-River Falls (University of Wisconsin-River Falls, 1960)
Online, digitized version of the Wisconsin State College, River Falls yearbook for 1960. The 1960 Meletean includes 160 pages of text and photographs.
Meletean 1960
160 p. divided into 5 parts: Part 1 = Cover and Pages 1-25; Part 2 = Pages 26-55; Part 3 = Pages 56-99; Part 4 = Pages 100-117; Part 5 = Pages 118-160 and Back Cover. Part 1 contains the introduction and photographs; Part 2 contains photographs of the Administration, Faculty and Staff and photographs of Special Events; Part 3 contains photographs and descriptions of Organizations on campus; Part 4 contains photographs and a description of Athletics on campus; and Part 5 contains individual class photographs. Editors: Judy Johnson and Pat Lind. Assistant Editors: Anne Adams, Carol Truttschel, Carol Korsmo. Sports Editor: Jon Hillstead. Photographers: Don Blegen, Wayne Harmann. Advisors: Jim Harless, Wayne Wolfe.
Keywords: College yearbook; 1960 year book; College year book; University yearbook; University of Wisconsin-River Falls--Students--Yearbooks; 1960 yearbook; University year book; University of Wisconsin-River Falls--Students--Yearbooks; School yearbooks--Wisconsin--River Falls; Class of 1960 year book; Class of 1960 yearbook; Year book; Yearbook